Strategic Formulation and Implementation of Drive Thru Service in Convenience Store - Fahmi, Fadhil; Wandebori, Harimukti (Journal of Business and Management, 2013)
This paper explains about the measurement of drive thru service importance on fast food restaurant business than others service. It will compared the revenue generated from drive thru service, numbers of drive thru customers, and also find out most important aspect of drive thru from customers perspective. This research use primary data from McDonald’s Dago, and also secondary data from the QSR 2012 study.--------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.